Identifying Critical Success Factors of Transformational Change in a Large Organization â€“ A Qualitative Analytical Approach - Lather, Anu Singh; Jain, Shilpa; Pandey, G. N.; Verma, Yogesh C. (Prabandhan: Indian Journal of Management, 2023)
Purpose : When it comes to managing organizational change, â€œhowâ€ is most important. This study is based on a real-world account of a major corporation that underwent a radical makeover and came out looking and feeling different. We found critical success variables that contribute to and facilitate this transformative process. Design/Methodology/Approach : The research study was data-driven, utilizing real data gathered from primary and secondary sources. The main technique used was the analytic hierarchy process. The results of two organizational climate surveys conducted before and after the change were confirmed and validated. Findings : This study aimed to determine the essential elements required for a transformation process to succeed. The topic of evaluating organizational health both before and after the transformational process is also touched upon, as is its efficacy. The findings point to the main issues that required attention in order to implement intervention for transformative change. Practical Implications : This study is of a large Indian PSU that embarked on an arduous and uncertain journey of corporate renaissance and metamorphosis. It may be of intense interest to other corporates to know about it. Many businesses preparing for significant transformations will gain insights from this article, which will also assist them in identifying favorable enabling elements and avoiding transformational traps. Originality/Value : This case concerned a well-known Maharatna PSU with substantial financial resources that is expanding quickly. Given that the business "rewired" the aircraft while it was in flight as a proactive measure, this case might be considered special. It was a first-hand narrative of the revolutionary shift that the organization had planned and carried out.